Animating Indian production culture: an interview with animation filmmaker and educator Ram Mohan (The South Asianist Journal, 2013)
Recent studies in global creative industries have helped reveal how media practitioners conceive professional identities and generate communities around cultural production. Nowhere is this more apparent than in the evolving space of Indian cinema, where the first century of filmmakers have not only devised vibrant industries but played key roles in conceiving national identity. Indian Animation, often misunderstood as a recent arrival, has roots early in this joint project of national development and entertainment. Filmmaker, educator and ‘father of Indian animation’ Ram Mohan has been active at every stage, and continues to contribute to a new Indian culture of animation filmmaking. In this interview Ram Mohan traces the rise of animation within Indian filmmaking across his long and varied career.